Emotional intelligence and leadership effectiveness in managing hybrid teams: A study of IT companies in Bengaluru - Rani, Chittarusu Radhika; Gowrappa, M. S; Pavithra, S; Lakshmi, S N (The International tax journal, 2026)
The concept of emotional intelligence has gained considerable importance in modern organizational leadership, particularly in hybrid work environments that emerged after the COVID-19 pandemic. The present study examines the relationship between emotional intelligence and leadership effectiveness in managing hybrid teams within IT companies located in Bengaluru. The study focuses on understanding how emotional intelligence dimensions such as self-awareness, empathy, motivation, self-regulation, and social skills influence employee engagement, communication effectiveness, team collaboration, and organizational trust in hybrid work settings. The research adopted a descriptive and analytical research design and utilized both primary and secondary data sources. Primary data were collected through a structured questionnaire administered to 178 employees, managers, HR professionals, and team leaders working in hybrid teams across Tata Consultancy Services, Infosys, Wipro, Oracle Corporation, and ABB. Statistical tools such as percentage analysis, mean, standard deviation, correlation analysis, regression analysis, and chi-square tests were used for data interpretation through SPSS and Microsoft Excel. The findings revealed a strong positive relationship between emotional intelligence and leadership effectiveness, indicating that emotionally intelligent leaders significantly improve employee engagement, communication quality, team collaboration, and organizational trust within hybrid work environments.